Political Communication : The Manship School Guide - Perlmutter, David D., 1962-; Mann, Robert, 1958- (Book collections on Project MUSE., 2011)
A new era of political power has arrived, one in which the social media forces of Facebook, YouTube, and Twitter indisputably play a larger role in the political process. In this revised and expanded edition of Political Communication: The Manship School Guide, edited by Robert Mann and David D. Perlmutter, contributors discuss technological changes in the context of studies and techniques that remain unchallenged, resulting in a truly comprehensive manual of the world of political communication.